Menghidupkan Kembali Tradisi Ijtihad di Era Modern Sebagai Solusi Problematika Umat Islam - Abd. Muqit (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Research with the title of reviving the tradition of ijtihad in the modern era uses library research methods, namely research that examines and searches for information and data that generally comes from written language that is related and relevant to the title being researched. The results of the research can be concluded that ijtihad in the contemporary era is a very significant need and cannot be separated from the problems of the people. Ijtihad is a solution to the problems of Muslims in dealing with social problems that occur in a society that is so complex and developing very rapidly. Ijtihad, which is seen by some Muslims as the door to exploring the law, of course has basic arguments from the Koran, Hadith and aqli. What needs to be underlined is that first, ijtihad is only within the scope of Sharia law, not other scientific knowledge. Second, the person who performs ijtihad is someone who is an expert in Fiqh who meets the requirements for a mujtahid. Thus, if someone is found who associates or uses the word ijtihad with his scientific endeavors which are not within the scope of Sharia law, then this is just ijtihad in language, not ijtihad as intended in the Sharia. Likewise, if someone claims to have done ijtihad but he has not fulfilled the requirements for ijtihad then his ijtihad is just a claim that he is not ijtihad in Islam, or he just wants to sweeten his language.